The Impact of The Manufacturing Companies’ Size on Cyber and Information Security - Lukas PODESVA; Milos KOCH; Michal MYSKA; Nikola SUNAVCOVA (Communications of International Proceedings, 2021)
This paper presents assessing the impact of the size of manufacturing companies on cyber and information security. Stated preliminary analysis was performed based on data obtained from the audit web tool ZEFIS and is intended to serve as a basis for further research in this area. In this analysis, 184 companies (which are not among the critical infrastructure) from the Czech Republic were evaluated in three main categories: ITC Security, Security Policy and User Behavior. The results show that a significant number of companies do not underestimate the threats posed by the development of communication and information technologies. The relationship between the size of the company (according to the number of employees) and the level of cyber and information security in the individual research areas was also identified. In general, as the size of the company grows, so does the level of cyber and information security.
Keywords: Information security; cyber security; security policy; manufacturing companies; information and communication technologies; ITC